Removal of 17β-Estradiol (E2) from Aqueous Solutions Using Potassium Permanganate Combined with Ultraviolet (KMnO4/UV) - Monirah Ataee; Abdolmajid Fadaei; Gashtasb Mardani; Morteza Sedehi (International Journal of Chemical Engineering)
17β-Estradiol (E2) has a significant health risk to humans, even at the ng/L level, and is discharged to the aqueous environment through wastewater. Advanced oxidation processes were proposed as an efficient process for the removal of E2. In this study, a combination of ultraviolet-C (UV-C) and KMnO4 was applied for the removal of E2. Results have shown that the removal efficiency of E2 in pH 4 (acidic condition) was 93.80 ± 0.42%. But, removal efficiency in neutral (7) and alkaline (10) conditions was 78.3 ± 2.12% and 84 ± 0.71%, respectively. The effect of Fe+2, Ca+2, Mg+2, Mn+2, and Fe+3 ions (1 mg/L) was investigated in optimized pH (4). Mn+2, Fe+2, and Ca+2 ions enhanced the removal efficiency to 94.8 ± 0.84%, 95.55 ± 0.07%, and 94.7 ± 0.14%, respectively p>0.05, while Mg+2 and Fe+3 ions decreased the removal efficiency significantly to 76.15 ± 1% and 83.91 ± 0.3% p<0.05. The efficiency of E2 removal in the presence of 5 mg/L of PAC reduced significantly to 85 ± 4.24% p<0.05. Also, humic substances like humic acid, fulvic acid, and a combination of them could enhance the efficiency to 99.87 ± 0.01%, 99.9 ± 0.06%, and 99.93 ± 0.014%, respectively p>0.05. The result indicates that the rate of oxidation of E2 is related to the second exponent of the initial concentration of E2 for optimum pH and the presence of all ions. But, in the presence of humic substances, the first-order kinetic reaction was best applicable in describing oxidation of E2. Removal of chemical oxygen demand for E2 after 120 minutes’ of contact time at optimum pH (86 ± 4.2%) demonstrated mineralization of these compounds at acceptable levels. Results presented that the UV-C/KMnO4 process is efficient for the removal of hormones from the aqueous solution.